Oliver Twist - Dickens, Charles, 1812-1870 (Oxford world's classics (Oxford University Press), 1999)
Oliver Twist is a classic tale of a boy of unknown parentage born in a workhouse and brought up under the cruel conditions to which pauper children were exposed in the Victorian England. With this novel, Dickens did not merely write a topical satire on the workhouse system and the role of the 1834 New Poor Law in fostering criminality. He created a moral fable about the survival of good, a romance, and a gripping story in which he exploited suspense and violence more effectively than any of his contemporaries. The new Oxford World's Classics edition of Oliver Twist is based on the authoritative Clarendon edition, which uses Dickens's revised text of 1846. It includes his preface of 1841 in which he defended himself against hostile criticism, and includes all twenty-four original illustrations by George Cruikshank. Stephen Gill's groundbreaking introduction gives a fascinating new account of the novel. He also provides appendices on Dickens and Cruikshank, on Dickens's Preface and the Newgate Novel Controversy, on Oliver Twist and the New Poor Law and on thieves' slang.